(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The method used in this research is a qualitative descriptive method. Qualitative descriptive research is a research procedure that produces descriptive data in the form of written, spoken words and observable behavior. The short story "Lorong Gelap" by Budi Darma presents the ethical values hat are important for life through the figure of Den Hardo, both the ethics of life in the family and the ethics of relationships between individuals in society. These ethical values include: ethics as a child in the family, ethics towards parents, and ethics towards siblings. The ethical values displayed in the short story "Beautiful Eyes" are ethics towards parents, namely mother, and ethics towards other people. The ethical values in the short story "Indah Mata" emphasize the ethics of the relationship between parents and children, namely the mother and Haruman. There are two ethical values in the short story "Tamu", namely children’s ethics towards other people and ethics towards parents.